2006
DOI: 10.1093/intimm/dxl053
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of BAFF in T cells of systemic lupus erythematosus, which is recapitulated by a human T cell line, Loucy

Abstract: B cell-activating factor of the tumor necrosis factor (TNF) family, or BAFF, is mainly produced in monocytes and dendritic cells, and indispensable for proliferation, differentiation and survival of B cells. BAFF is a type II membrane-bound protein and the extracellular C-terminal fragment is released from the cells as soluble BAFF (sBAFF), which binds to specific receptors on B cells. Accumulating evidence suggests that BAFF plays an important role in the pathogenesis of autoimmune diseases, such as systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 43 publications
(32 reference statements)
1
37
2
Order By: Relevance
“…Indeed, in patients with SLE even T cells express abundant BAFF, in particular when they are activated (25). Attempts to correlate disease activity with the titer of circulating BAFF have largely failed, although a correlation between disease activity and the levels of BAFF and APRIL messenger RNA (mRNA) in whole blood cells has been shown (1,2,5).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in patients with SLE even T cells express abundant BAFF, in particular when they are activated (25). Attempts to correlate disease activity with the titer of circulating BAFF have largely failed, although a correlation between disease activity and the levels of BAFF and APRIL messenger RNA (mRNA) in whole blood cells has been shown (1,2,5).…”
Section: Discussionmentioning
confidence: 99%
“…Yoshimoto et al [47] reported that the inhibitors of p38 and JNK inhibited sBAFF production in 12-Otetradecanoylphorbol 13-acetate-and ionomycin-stimulated Loucy, a human T cell line. However, they showed only sBAFF secretion by ELISA [47]. Therefore, to verify the difference in data between the two analytical methods, we additionally analyzed it by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…6B). It has been known that sBAFF release is mediated by furin [4,32,46,47]. Therefore, to evaluate whether the JNK and p38 signaling pathways are involved in furin expression, we performed Western blot analysis.…”
Section: The Release Of Sbaff In Gmix-treated Bv-2 Cells Is Dependentmentioning
confidence: 99%
“…BAFF/BLyS production by T cells was previously shown in patients with systemic lupus erythematosis. 38 In non-autoimmune mouse strains, BAFF/BLyS is produced mostly by dendritic cells and macrophages. 39 The presence of a large percentage of T cells producing BAFF/BLyS when NZB/W mice were injected with IgG2a may constitute a deregulation of BAFF/BLyS production as the result of an inherent over/ underexpression of a special class of molecules belonging to the Fc c-receptor family in those mice.…”
Section: Discussionmentioning
confidence: 99%